Process of Decision-Making Divorces on Women Who Are Undergoing Pregnancy in The First Year of Marriage - Solichah, Novia; Istiqomah, Adinda (International Conference on Sustainable Health Promotion, 2018)
This study aims to find out how the process of decision-making divorced in women who are undergoing pregnancy in their first year of marriage? Are the factors that influence the subject taking a divorce decision? This study uses qualitative research methods with a phenomenological approach. Subjects in the study were women aged 20-30 years, were pregnant, and filed for divorce with their husbands. Data collection is done by open and in-depth interviews. Data analysis uses data-driven and credible consolidation techniques over research using member checking. The results showed that the factors that caused him to decide to divorce were influenced by twelve factors, namely financial problems, work, family influences, habits, changes in attitudes and behavior, perception of marriage, commitment before marriage, place of residence, husband’s role, knowledge of the risk of divorce, trust, and health problems. These twelve factors are then categorized into internal and external factors. The dominant internal factors that influence the subject in taking divorce decisions are the subject’s perception of marriage, while the most dominant external factors are family environmental factors. The subject decision-making process consists of three stages, namely diagnosis, selection of actions, and implementation. These three processes repeatedly occur in each problem. Some problems arise in marriage, then determine that the marriage is problematic and does not run like a marriage in general.